2016
DOI: 10.33524/cjar.v17i3.286
|View full text |Cite
|
Sign up to set email alerts
|

Through a Feminist Poststructuralist Lens: Embodied Subjectivites and Participatory Action Research

Abstract: An emerging literature has been building bridges between poststructuralism and participatory action research, highlighting the latter’s potential for transformative action. Using examples from participative action research projects with incarcerated or previously incarcerated women, this article discusses how participatory action research is a methodology that can be enabling and restraining, with the effect of destabilising or maintaining or existing relations of power. Theorizing embodied subjectivity as a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…We found that micro‐practices of power can extend to mutuality in ‘caregiving’ where relations of power are reconfigured through reciprocity (Chesnay, 2016 ). Surprisingly, the notion of ‘caregiving’ as bidirectional and mutual (Groot et al., 2019 ), drawn from Tronto’s ( 2013 ) ‘second‐generation ethics of care’, is not often written about in PAR studies though it was apparent in our interactions.…”
Section: The Praxis Of Par: Collectivity and Complicitymentioning
confidence: 99%
“…We found that micro‐practices of power can extend to mutuality in ‘caregiving’ where relations of power are reconfigured through reciprocity (Chesnay, 2016 ). Surprisingly, the notion of ‘caregiving’ as bidirectional and mutual (Groot et al., 2019 ), drawn from Tronto’s ( 2013 ) ‘second‐generation ethics of care’, is not often written about in PAR studies though it was apparent in our interactions.…”
Section: The Praxis Of Par: Collectivity and Complicitymentioning
confidence: 99%